German Theater at Northern American Colleges and Universities 1992 - 2006 - Matthias, Bettina (SCENARIO: Journal for Performative Teaching, Learning, Research, 2008)
This article presents results from the latest survey on German theater at Northern American colleges and universities. The survey covers the period since the last such query in 1991 until 2006. It assesses a growth in theater productions in German and the logistics surrounding them, and it lists the most performed plays and the most popular authors performed. Finally, the article identifies areas of concern for those working in German theater at academic institutions and invites interested colleagues to join a newly established network that serves to facilitate the exchange of ideas, cooperation, and recognition of foreign language theater as a key contribution to a language program’s offerings. This article presents results from the latest survey on German theater at Northern American colleges and universities. The survey covers the period since the last such query in 1991 until 2006. It assesses a growth in theater productions in German and the logistics surrounding them, and it lists the most performed plays and the most popular authors performed. Finally, the article identifies areas of concern for those working in German theater at academic institutions and invites interested colleagues to join a newly established network that serves to facilitate the exchange of ideas, cooperation, and recognition of foreign language theater as a key contribution to a language program’s offerings.